Leadership Strategies in Resolving Organizational Conflicts - Chasan Ma’ruf; Ach. Baidowi; Wan Khairul Aiman Wan Mokhtar; Mega Suteki (Penerbit Goodwood, 2026)
Purpose: This study aims to formulate a new theory on leadership strategies for overcoming organizational conflicts, based on established theories of leadership strategy and organizational conflict. Methodology/approach: This research used a qualitative approach with a literature review. Data collection techniques involved document analysis of journal articles and internet sources. Data validity was ensured through the triangulation of sources. Results: Leadership strategy focuses on planning, decision-making, and motivating people to achieve organizational goals while remembering that leaders must stay adaptive and innovative. Organizational conflicts often arise from differences in resource allocation and goals. Resolving conflict requires empowering human resources through methods such as focus group discussions, job rotation, dismissal, and collaboration, depending on the impact on performance. Limitations: The research findings cannot be generalized to all organizations and offer limited discussion of contextual dynamics, such as culture, structure, and external factors that influence the success of leadership strategies in resolving conflicts. Contributions: This study formulates a new theory on leadership strategies for resolving organizational conflicts by integrating two major theories. The findings expand the understanding of a leader's role in planning, decision-making, motivation, and inspiration in managing organizational conflicts effectively. Contributions: This research develops a new leadership theory for resolving organizational conflicts by integrating leadership, planning, and adaptive strategies, including focus group discussions, job rotation, and collaboration.